Digital Transformation of Learning in Islamic Boarding Schools in The Society 5.0 Era: A Qualitative Study on Enhancing Educators' Digital Competence - Ismail Marzuki; Yayan Sudrajat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
The purpose of this study is to describe the digital transformation process of learning at the At-Thahiriyah Kaloran Islamic Boarding School in Serang City as a response to the demands of education in the Society 5.0 era. Digital transformation in Islamic boarding schools is necessary to integrate traditional values ​​with breakthroughs in learning technology. This study uses a qualitative approach and descriptive-analytical methods with field research qualifications. Data obtained through interviews, observations, and documentation are then processed analytically using the Miles and Huberman model of data reduction, data presentation, and conclusion drawing. The results show that the At-Thahiriyah Islamic Boarding School implements digital learning through digital literacy training for students, both internal and external, the provision of internet-based computer laboratories, and the use of social media or websites as learning and promotional media for the institution. However, the digital transformation process also faces obstacles in the form of uneven quality of human resources in managing digital systems and limited costs for maintaining a number of technologies. The conclusion of the study is that the digital transformation of Islamic boarding schools equires improving the digital competence of educators adaptive managerial policies, and strengthening the digital literacy of students so that religious values ​​and the dynamics of the technological era are balanced.